The reformation of emotions in the age of Shakespeare - Mullaney, Steven (The University of Chicago Press, 2015)
Structures of feeling and the reformation of emotions -- Affective irony in the Spanish tragedy, Titus Andronicus, and the Merchant of Venice -- The wreckage of history: memory and forgetting in Shakespeare's first history tetralogy -- What's Hamlet to Habermas? : theatrical publication and the early modern stage